Mario Puzo's The godfather [videorecording (DVD)] - Coppola, Francis Ford, 1939-; Coppola, Francis Ford, 1939-; Brando, Marlon; Pacino, Al, 1940-; Caan, James; Castellano, Richard, 1933-1988; Duvall, Robert; Hayden, Sterling, 1916-1986; Conte, Richard, 1910-1975; Keaton, Diane; Shire, Talia; Cazale, John, 1936-1978; et al. (Paramount Home Entertainment, 2008)
"Don" Vito Corleone is the head of a New York mafia 'family.' His beloved son Michael has just come home from the war, but does not intend to become part of his father's business. Not given a choice, the business of the family is just like the head of the family, kind and benevolent to those who give respect, but gives in to ruthless violence whenever anything stands against the good of the family. An up and coming rival of the Corleone family wants to start selling drugs in New York, and needs the Don's influence to further his plan. A clash of old world values and the new ways will exact a terrible price, especially from Michael.